Correlation between physician assistant students’ performance score of history taking and physical exam documentation and scores of Graduate Record Examination, clinical year grade point average, and score of Physician Assistant National Certifying Exam in the United States - Sara Lolar; Jamie McQueen; Sara Maher (Journal of Educational Evaluation for Health Professions, 2020)
Purpose Learning to perform and document patient history taking and physical exam (H&P) entails a major component of the first year academic education of physician assistant (PA) students at Wayne State University, USA. The H&P is summative of multiple aspects of PA education, and students must master communication with patients and other health care providers. The objectives of this study were first, to determine if there was a correlation between scores on the Graduate Record Examination (GRE) component testing and scores on graded H&Ps. The second objective was to identify a correlation between proficiency with H&P documentation and academic and clinical year grade point average (GPA) and Physician Assistant National Certifying Exam (PANCE) score. Methods Subjects included 147 PA students from Wayne State University from 2014–2016. PA students visited local hospitals or outpatient clinics during the academic year to perform and document patient H&Ps. Correlation between the H&P mean scores and GRE component scores, GPAs, and PANCE scores were analyzed. Results The subjects were 26.5 years-old (+6.5) and 111 females (75.5%). There was no correlation between the GRE component score and the H&P mean score. The H&P score was positively correlated with GPA 1 (r=0.512, P<0.001), with GPA 2 (r=0.425, P<0.001) and with PANCE score (r=0.448, P<0.001). Conclusion PA student skill with H&P documentation was positively related to academic performance score during PA school and achievement score on the PANCE at Wayne State University, USA.